Microtubules CLASP to Adherens Junctions in epidermal progenitor cells - Shahbazi, Marta N (Landes Bioscience, 2014)
Cadherin-mediated cell adhesion at Adherens Junctions (AJs) and its dynamic connections with the microtubule (MT) cytoskeleton are important regulators of cellular architecture. However, the functional relevance of these interactions and the molecular players involved in different cellular contexts and cellular compartments are still not completely understood. Here, we comment on our recent findings showing that the MT plus-end binding protein CLASP2 interacts with the AJ component p120-catenin (p120) specifically in progenitor epidermal cells. Absence of either protein leads to alterations in MT dynamics and AJ functionality. These findings represent a novel mechanism of MT targeting to AJs that may be relevant for the maintenance of proper epidermal progenitor cell homeostasis. We also discuss the potential implication of other MT binding proteins previously associated to AJs in the wider context of epithelial tissues. We hypothesize the existence of adaptation mechanisms that regulate the formation and stability of AJs in different cellular contexts to allow the dynamic behavior of these complexes during tissue homeostasis and remodeling.